CONTEMPORARY FUNDAMENTALISM AND FJM POTGIETER’S THEOLOGY - Engdahl, Hans S. A. (Scriptura, 2011)
In this article Afrikaner theology articulated by FJM Potgieter is compared to contemporary fundamentalism. Potgieter’s theology is built on certain biblical principia that represent revealed truth and therefore are irreducible principles applicable in all spheres of life. These principles are also confirmed by common grace in the God-given dispensation of peoples and races. Contemporary fundamentalism would often begin with a select tradition that is strictly applied to the present. Often it is about a religious tradition that is used as a means to a political outcome. The article argues that Potgieter’s theology has unmistakable elements of such contemporary fundamentalism.